Flame Propagation Analysis of Laser Induced Combustion of CH4-Air Mixture in a CVCC - C. D. Koshti11, M. R. Nandgaonkar (International Journal of Advanced Science and Technology, 2020)
This paper present combustion of premixed homogeneous mixture of methane-air initiated by a spark, developed by focusing laser light in a CVCC (constant combustion chamber).The Nd: YAG laser with 1064nm wavelength and pulse width of 5.5ns focused into 80mm X 180mm cylindrical chamber through a Plano-convex lens having 125mm focal length. The experiments are carried out with 7.5 bar initial pressure at ambient conditions and mixtures with an equivalence ratios ranging from 0.7 to 1.2 with an increment of 0.1. The mixtures were ignited using minimum laser pulse energy measured by pyro-electric energy meter and flame propagation images in early stages of combustion were captured using high speed camera. The captured images were calibrated and flame front radius measured with respect to time using image processing software i-speed suite. For each equivalence ratio, stretched and unstretched flame propagation speed, global stretch rate and Markstein length are calculated. The values of unstretched flame propagation speed and laminar burning velocity are found maximum at  = 1 with 190 cm/s and 22.81 cm/s respectively. At  = 0.7 and  = 1.2, the values of laminar burning velocity are 15.6 cm/s and 19.12 cm/s respectively. The Markstein lengths were positive and increasing with increase in equivalence ratio. At  = 0.7 to  = 1.2, the Markstein length increases from 0.89 mm to 2.2 mm which means the stability of the flame increases with the increase of equivalence ratio